Topological grounds for the fast kinematic dynamo origin in a knotted thermonuclear reactor - Maksyuta, M.V.; Golovach, G.P.; Martysh, Ye.V. (Вопросы атомной науки и техники, 2013)
The paper deals with the topological grounds for the possibility of effective fast kinematic dynamo origin in socalled knotted thermonuclear reactors. On the basis of the utilization of the topologic spirality invariant the additional arguments in favour of plasma strings stability raise in such reactors are given. It is supposed that in the reactors with cavities like linking torical knots plasma confinement characteristics may be essentially improved that would allow carrying out thermonuclear synthesis. Проводится топологическое обоснование возможности возникновения эффективного быстрого кинематического динамо в так называемых заузленных термоядерных реакторах. На основе использования топологического инварианта спиральности приводятся дополнительные аргументы в пользу повышения устойчивости плазменных потоков в таких реакторах. Высказываются предположения, что для реакторов с полостями в виде зацепленных торических заузленностей характеристики удержания плазмы могут резко улучшиться, что позволило бы осуществить термоядерный синтез. Проводиться топологічне обгрунтування можливості виникнення ефективного швидкого кінематичного динамо в так званих завузлених термоядерних реакторах. На основі використання топологічного інваріанта спіральності приводяться додаткові аргументи на користь підвищення стійкості плазмових потоків у таких реакторах. Висловлюються припущення, що для реакторів з порожнинами у вигляді зачеплених торічних завузленостей характеристики утримання плазми можуть різко покращитися, що дозволило б здійснити термоядерний синтез.